Anatomy of a Temporary Trade Shock: The Kenyan Coffee Boom of 1976-9. - Bevan, D; Collier, P; Gunning, J (1992)
The coffee boom of 1976-9 was an archetypal temporary external shock. Using counterfactuals, we find that much of the windfall was saved, due to the private sector. However, the control regime constrained private responses, leading to an inefficient use of the windfall. Rather than Dutch Disease there was a construction boom.